(untitled) (XXI Century. Spanish Literature and Culture, 2004)
Through a comparison, Virginia Trueba Mira gathers together the works and thoughts of Valente and Tàpies, focusing on aspects such as the light, always referred to as creating light; fragmentism that offers a more approachable vision of the world or the aesthetics of poverty and Valente’s new vision, of whom she says does not copy his artistic reference but considers the formation of the painting-body, which is, its vertex.